Growth and development time of subtropical Cladocera Diaphanosoma birgei Korinek, 1981 fed with different microalgal diets - Sipaúba-Tavares, Lúcia Helena [UNESP]; Truzzi, Bruno Scardoeli [UNESP]; Berchielli-Morais, Flávia de Almeida [UNESP] (Int Inst Ecology, 2014)
The aim of this work was to investigate the growth performance of Diaphanosoma birgei fed with two Chlorophyceae algae, Ankistrodesmus gracilis and Haematococcus pluvialis using monoalgal diets and simpler mixed diets. D. birgei was daily fed on four treatments: 1) 100% Ankistrodesmus gracilis (Ag); 2) 100% Haematoccocus pluvialis (Hp); 3) 25% A. gracilis + 75% H. pluvialis (Ag-25+Hp-75) and 4) 75% A. gracilis + 25% H. pluvialis (Ag-75+Hp-25). The fecundity curve of D. birgei showed that the mixed feed Ag-25+Hp-75 and temperature 24 +/- 2 degrees C triggered fast fecundity at approximately two days. The fecundity was low when based only on H. pluvialis (Hp), albeit with greater longevity (19 days) and a higher number of broods (8). D. birgei fed on Ag and Ag-75+Hp-25 diets in this experiment sustained higher growth rate and higher lipid content in these treatments. The present study showed that A. gracilis diet and mixed microalgae diets tested were able to support the egg production and development of D. birgei.

O objetivo deste estudo foi avaliar o crescimento de uma espécie de Cladocera Diaphanosoma birgei alimentada com dois tipos de microalgas Chlorophyceae, Ankistrodesmus gracilis e Haematococcus pluvialis cultivadas em monocultura e cultura mista. Quatro dietas foram utilizadas: 1) 100% Ankistrodesmus gracilis (Ag); 2) 100% Haematoccocus pluvialis (Hp); 3) cultura mista com 25% A. gracilis + 75% H. pluvialis (Ag-25+Hp-75) e 4) cultura mista com 75% A. gracilis + 25% H. pluvialis (Ag-75+Hp-25). A curva de fecundidade de D. birgei mostrou que a dieta mista Ag-25+Hp-75 e temperatura de 24±2°C promoveu rápida fecundidade em aproximadamente dois dias. A fecundidade foi baixa quando D. birgei foi alimentada somente com H. pluvialis (Hp), porém foi observada maior longevidade (19 dias) e consequentemente, maior número de descendentes (8). As dietas Ag and Ag-75+Hp-25 apresentaram efeito direto na taxa de crescimento de D. birgei com elevados teores de lipídios nestes tratamentos. O presente estudo mostrou que as dietas contendo somente A. gracilis e as dietas mistas de microalgas foram capazes de manter níveis adequados na produção de ovos e no desenvolvimento de D. birgei.
Crescimento e tempo de desenvolvimento de uma espécie de Cladocera subtropical Diaphanosoma birgei Korinek, 1981 alimentada com dietas de microalgas
Keywords: Ankistrodesmus gracilis; Haematococcus pluvialis; Monoalgal diets; Mixed diets; Growth rates; Ankistrodesmus gracilis; Haematococcus pluvialis; Dietas de monocultura de algas; Dietas mistas; Taxas de crescimento